Functional Equation of the P-Adic L-Function of Bianchi Modular Forms - Palacios-Moyano, L (Academic Press, 2023)
Let K be an imaginary quadratic field with class number 1, in this paper we obtain the functional equation of the p-adic L-function of small slope p-stabilised Bianchi modular forms. Then, using p-adic families of Bianchi modular forms, we extend our result to Σ-smooth base-change Bianchi modular forms. © 2022 Elsevier Inc.